Endovascular Repair of a Penetrating Axillary Artery Injury - Altoijry, Abdulmajeed (Braz J Cardiovasc Surg, 2019)
We report a 16-year-old boy who sustained a gunshot injury on his upper left side of the chest that resulted in an injury to the left axillary artery and was treated with endovascular repair. An endovascular repair has been increasingly accepted for the management of hemorrhage in critically ill trauma patients; using covered endovascular stents provides an alternative modality for both controlling hemorrhage and preserving flow.